Prevalence of target organ damage in subjects with high-normal blood pressure without known cardiovascular and kidney disease. (14th October 2021) - Ruzzenenti, G; Maloberti, A; Rebora, P; Occhino, G; Alloni, M; Musca, F; Belli, O; Spano', F; Santambrogio, G M; Casadei, F; Moreo, A; Valsecchi, M G; et al.
Abstract: Background: Heterogeneous results have been obtained regarding the presence of Target Organe Damage (TOD) in subjects with high-normal Blood Pressure (BP) value (sistoly 130–139, diastolic 85–89 mmHg). Purpose: Aim of our study was to assess the prevalence of TOD in healthy subjects with high-normal BP comparing them with subjects with BP values that are considered normal (<130/85 mmHg) or indicative of hypertension (≥140/90 mmHg). Methods: 755 otherwise healthy subjects participated at the present analysis. TOD was evaluated as Pulse Wave Velocity (PWV), Left Ventricular Mass Index (LVMI) and carotid Intima-Media Thickness (IMT) and plaque. Results: When subjects were classified according to BP levels we found that high-normal BP group showed intermediate values of PWV and LMVI with higher value of IMT. This corresponds to intermediate prevalence of arterial stiffness (PWV>10 m/s: 3.4% vs 2.3% for normal and 9.6% for high BP groups, p=0.0014), Left Ventricular Hypertrophy – LVH (32.4% vs 25.7% for normal and 46.6% for high BP groups, p=0.0001) while there were no differences for IMT>0.9 or carotid plaque. At multivariable analysis the odds of having a PWV>10 m/s (OR=1.75, 95% C.I. 0.59–5.16), an IMT>0.9 mm (OR=1.81, 95% C.I. 0.60–5.00) or a LVH (OR=1.1, 95% C.I. 0.72–1.67) in the high-normal group resulted not different to the normal group. Conclusions: In our otherwise healthy population, high-normal BP values were not related to aortic, carotid or cardiac TOD. FUNDunding Acknowledgement: Type of funding sources: None.